Diseño e implementación de un sistema informático de historias clínicas para el Hospital provincial general Isidro Ayora de Loja, que integre las áreas de consulta externa, hospitalización y emergencia. - Armijos Merino, Richard Francisco (2010)
This research project aims to make the creation and registration of medical records of patients in the "Hospital Provincial General Isidro Ayora de Loja" in order to support the department "Aseguramiento de la Calidad" and areas "Consulta Externa", "Hospitalizacion" and "Emergencia", for that these departments have a quick and efficient access to information for patients seen at this institution. Thus, our work is a Hospital Management System, which allows systematically organizing patient information, delivering shifts for all specialties, and using the information stored in all areas of the hospital. To develop the application we use investigative techniques that allowed collecting all the information needed for the analysis and determining what are the different problems that it takes management of clinical records and use of information in different areas of the hospital. This system is built on the Web platform, developed and implemented with ICEfaces Framework and as regards the storage of data we used the MySQL database v5.0.